Effect of Cement Dust Exposure duration on Liver Function Parameters in Cement Factory Workers - Aindrila Das Gupta,; Momtaz Begum,; Shahin Akhter,; Debjane Baru,; Md Mujahidul Islam,; Uschash Karan, (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Production of cement is a dusty industrial process which includes emission of particulates, gases, solid waste, etc. Cement industries are regarded as one of the major source of environmental pollution. Cement factory workers are prone to occupational hazards. They encounter detrimental impact on their health due to prolong and repeated exposure to cement dust. This study was aimed at evaluating the effect of cement dust exposure duration on liver function parameters (Serum bilirubin, alanine aminotransferase, aspartate aminotransferase and alkaline phosphatase) in cement factory workers. Materials and methods: Across-sectional comparative study design was adopted in this work. It was conducted in Department of Physiology, Chittagong Medical College in collaboration with Confidence cement factory Ltd. Chattogram from July 2022 to June 2023. Apparently healthy total 96 male subjects, aged between 20-50 years with BMI 18.5-27.5kg/m2 were included in this study by simple random sampling using lottery technique. Among them 48 cement factory workers, who were directly exposed to cement dust for at least 5 years and 48 subjects, engaged in desk job/office work, not directly exposed to cement dust in their working environment were enrolled in this study. To assess liver function serum ALT, AST, ALP and serum bilirubin were estimated. Unpaired Student’s t-test and ANOVA test were done for statistical analysis. Results: Mean values of serum ALT and AST were significantly higher in workers exposed for 10-14 years. Other parameters showed non significant changes between groups. Conclusion: The results of this study suggests that duration of exposure to cement dust might not cause significant differences in the liver function of cement factory workers. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 47-51